2011
DOI: 10.3109/02688697.2011.584986
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-infiltrating T-cell subpopulations in glioblastomas

Abstract: This study was designed to determine the incidence and prognostic value of various populations of tumour-infi ltrating T cells in glioblastomas. We also evaluated the diff erence in T-cell populations after conventional treatment. Sixty-seven patients with glioblastomas underwent surgery between 2003 and April 2009. Immunohistochemical staining was performed for CD3, CD4, CD8 and FoxP3, and the average number and percentage of positive cells were calculated. In eight patients, the average number of subpopulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 29 publications
11
41
1
1
Order By: Relevance
“…With respect to tumor T-cell infiltrates in glioma tissue, our results are consistent with the published literature in several significant ways. Similar to previous reports, we found that T-cell and Treg infiltrates in tumor tissue increase with glioma grade, 10,43 that the fraction of Tregs/T-cells was increased in glioma tissues compared with blood implicating an active infiltration and accumulation in tumor tissue, and we found that CD8 cells represent about 60% of the T-cells in GBM tissues compared with 77% 44 or 40% 43 in previous studies. Hussain et al reported that CD8 cells were about 30% of identified T-cells but their study acknowledge significant problems with autofluorescence in their flow analysis making the identification of CD4 cells problematic.…”
Section: Methodssupporting
confidence: 80%
“…With respect to tumor T-cell infiltrates in glioma tissue, our results are consistent with the published literature in several significant ways. Similar to previous reports, we found that T-cell and Treg infiltrates in tumor tissue increase with glioma grade, 10,43 that the fraction of Tregs/T-cells was increased in glioma tissues compared with blood implicating an active infiltration and accumulation in tumor tissue, and we found that CD8 cells represent about 60% of the T-cells in GBM tissues compared with 77% 44 or 40% 43 in previous studies. Hussain et al reported that CD8 cells were about 30% of identified T-cells but their study acknowledge significant problems with autofluorescence in their flow analysis making the identification of CD4 cells problematic.…”
Section: Methodssupporting
confidence: 80%
“…43 Although a remarkable amount of tumor-infiltrating lymphocytes (TIL) seems to be tumor-antigen specific, most of them do not execute any effector functions or contribute to tumor regression -they virtually have been rendered silent. [44][45][46] Especially, highgrade gliomas have been shown to suppress, modulate and evade the immune system at multiple levels. 27,41 Hereby the tumor not only alters its immunological appearance, but also plays an active role by manipulating the immune system in its favor.…”
Section: Tumor Evasion and Immunosuppressionmentioning
confidence: 99%
“…Although the role of various factors involved in the immune response on clinical evolution of glioma patients is suggested by a number of studies, the specific role of Treg in GBM progression requires further investigations [13,14,22]. In fact, while the study by Kim did not show a predictive value of FOXP3 expression in tumor specimens on progression and survival in a group of 67 GBM patients [22], the study from Fig.…”
Section: Discussionmentioning
confidence: 43%
“…In fact, while the study by Kim did not show a predictive value of FOXP3 expression in tumor specimens on progression and survival in a group of 67 GBM patients [22], the study from Fig. 2 a Mean migration ratios of Treg in patients (GBM) and healthy controls (CTR).…”
Section: Discussionmentioning
confidence: 99%